EVALUASI PELAKSANAAN PROYEK BANGUNAN PEMERINTAHDITINJAU DARI SEGI WAKTU PELAKSANAAN DI KABUPATENSLEMAN DIY TAHUN 2011 - Bada Haryadi, Imam Muchoyar (Universitas Negeri Yogyakarta, 2012)
The aim research are (1) Delay in the implementation of the project; (2) Thebank capital; (3) materials of project; (4) relationship betwen Owner, projectconsultant, and contractor. This research was conducted in Sleman Daerah IstimewaYogyakarta. The sampleof this research is 15 person, with random sampling. Thedata of Analysis using Descriptive of quantitative and percentage. The result aredelay in the implementation of the project, the bank capital were 38.5% and 53.3%respectively. The relationship betwen Owner, project consultant, and contractor werethe result 43,8%. Thats means the relationship is unfavourable.Keyword: project, relationship